Tourism Entrepreneurship Performance - Assaker, Guy (2015)
Drawing on theories from environmental psychology, social psychology, and entrepreneurship, this study examines a nonrecursive (simultaneous equation) model of entrepreneurs’ place identity, entrepreneurial self-efficacy, and performance across male and female tourism entrepreneurs. Data were collected from 150 male and 148 female tourism business owners in Australia. The results found that place identity (sense of identity with their town of residence) was positively related to entrepreneurial self-efficacy (beliefs in their capabilities as entrepreneurs). Furthermore, self-efficacy is a direct driver of performance, and not vice versa, for both male and female entrepreneurs. However, multigroup invariance analysis suggests that the nonrecursive model is partially moderated by the entrepreneurs’ gender. The relationship between entrepreneurial self-efficacy and performance was significantly greater for the male group. The findings have implications for scholars in tourism and entrepreneurial studies, and for policy makers trying to support the sustainable development of tourism destinations.